Metafora "Joga to podróż" - Jurewicz, Joanna (Gajt Wydawnictwo 1991 s.c., 2018)
In the paper, I investigate the metaphor of yoga (yoga is a journey) which is attested in the early Brahminic texts, beginning already in the Ṛgveda where yóga means „journey”. In the Upaniṣads and the Smṛti texts, the experience of journey with its many details is evoked to describe the complex and dangerous nature of yoga. The coherence and continuity in the conceptualisation of yoga can also be seen in that journey was seen as an activity which leads to freedom already in the Ṛgveda. On more general level, the results of the research presented in the paper can be explained within the frames of Gadamer’s theory of the effective influence of tradition and the fusion of horizons, the past and the present ones, thanks to which culture remains in a constant dialogue with its earlier background and is redefined, refreshed and enlivened by it.
Keywords: yoga; Ṛgveda; Upaniṣads; Bhagavadgītā; Mahābhārata